2014
DOI: 10.1001/jama.2014.4144
|View full text |Cite
|
Sign up to set email alerts
|

The Familial Risk of Autism

Abstract: Importance Autism Spectrum Disorders (ASD) aggregates in families, but the individual risk and to what extent this is caused by genetic factors, or shared or non-shared environment remains unresolved. Objective To provide estimates of familial aggregation of ASD. Design, Setting and Participants A population based cohort of all Swedish children born 1982–2007. We identified all twins, full siblings, maternal and paternal half siblings and cousin pairs and all diagnosis of ASD to 31-December-2009. Main Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
685
1
33

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 933 publications
(738 citation statements)
references
References 34 publications
19
685
1
33
Order By: Relevance
“…Previous theory also predicted a preferred role for the mother in transmission, based largely on the reduced incidence of autism in females. Earlier population studies have indicated the importance of a shared maternal bloodline in sibling risk (19,20). In support of these reports, we find that the majority of the signal of biased transmission of UR LGD variants in vulnerable genes comes from the maternal line.…”
Section: Discussionsupporting
confidence: 88%
“…Previous theory also predicted a preferred role for the mother in transmission, based largely on the reduced incidence of autism in females. Earlier population studies have indicated the importance of a shared maternal bloodline in sibling risk (19,20). In support of these reports, we find that the majority of the signal of biased transmission of UR LGD variants in vulnerable genes comes from the maternal line.…”
Section: Discussionsupporting
confidence: 88%
“…Despite the high prevalence of ASD (recent reports indicate that as many as 1 in 68 children are born with ASD), a specific etiology is identified in <20 % of patients (as reviewed in [26]). Notwithstanding, there is a significant genetic component to ASD, as illustrated by the observation that 1) risk of recurrence is approximately 20 % for siblings, and 2) concordance for autism in monozygotic twins is 8 times higher than in dizygotic twins [27][28][29][30][31]. For this reason, considerable effort has been invested into identifying human genetic causes of ASD.…”
Section: As and Autismmentioning
confidence: 99%
“…It is multifactorial in background with high heritability (Sandin et al 2014) and the underlying neurobiological mechanisms have yet to be determined. Current research is looking at gene-environment interaction models to explain the etiology and also the variations in phenotypic expression (Chaste and Leboyer 2012).…”
Section: Discussionmentioning
confidence: 99%